ENTREPRENEURIAL MINDSET: PROGRAM PENINGKATAN KREATIVITAS DAN INOVASI ANAK MUDA MELALUI EDUKASI EKONOMI KREATIF DAN PENGEMBANGAN HOBI - Saqinaturrohimah; Larasati; Ulandari Yeni Zulian (Abdi Jurnal Publikasi, 2026)
This Community Service Program (PKM) aims to enhance youth creativity and innovation through creative economy education and hobby development as productive economic potential. This program was implemented as part of the Memorandum of Understanding (MOU)/Cooperation Agreement (MOA/PKS) between Universitas Pamulang and SMAIT An Nawawi Al Bantani Number: 041033/IA/2025/28615. The activity was conducted on Sunday, November 9, 2025, at SMAIT An Nawawi Al Bantani. The implementation method was participatory, educational, and applicative through material, presentations, interactive discussions, and mentoring in developing hobby-based ideas. The results indicate an increased understanding of creative economy concepts and growing awareness among students that hobbies can be transformed into economically valuable business opportunities. This program contributes positively to fostering creative, innovative, and independent mindsets among students in preparing for future economic challenges.